Associations of Thyroid Hormones Profile During Normal Pregnancy and Postpartum With Anxiety, Depression, and Obsessive/Compulsive Disorder Scores in Euthyroid Women - Konstantakou, Panagiota; Chalarakis, Nikos; Valsamakis, Georgios; Sakkas, Evangelos Grigoriou; Vousoura, Eleni; Gryparis, Alexandros; Sakkas, Grigorios Evangelou; Papadimitriou, George; Zervas, Ioannis; Mastorakos, George (Frontiers in Neuroscience, 2021)
Objective Thyroid dysfunction (overt and subclinical) has been consistently linked to pregnancy adversity and abnormal fetal growth and development. Mood disorders such as anxiety, depression, and obsessive-compulsive disorder (OCD) are frequently diagnosed during pregnancy and at postpartum, and emerging evidence suggests association with impaired offspring neurodevelopment and growth. This study aimed to examine potential associations between thyroid function and mood symptoms during pregnancy and postpartum. Design This is a prospective study measuring thyroid hormones and assessing mood symptoms by employing specific questionnaires in the same cohort of 93 healthy pregnant women at the 24th (2nd trimester) and 36th (3rd trimester) gestational weeks and at the 1st postpartum week. Methods Serum thyroid hormones, TSH, anti-TPO, and anti-Tg antibodies were measured at the 24th (2nd trimester) and 36th (3rd trimester) gestational weeks and at the 1st postpartum week. Specific validated questionnaires were employed at the same time-points to assess separately symptoms of anxiety [Generalized Anxiety Disorder Inventory (GADI), Penn State Worry Questionnaire (PSWQ), STAI-State Anxiety inventory (STAI-S), STAI-Trait Anxiety Inventory (STAI-T)], depression [Edinburgh Postnatal Depression Scale (EPDS), Stein’s Blues Scale (BLUES), Beck Depression Inventory (BDI)], and obsessive compulsive disorder (OCD) [Yale-Brown Obsessive Compulsive scale (Y-BOCS)]. Results At the 2nd trimester, GADI score correlated negatively with FT3 (p < 0.010, r = −0.545) and positively with TSH (p < 0.050, r = 0.837) concentrations; GADI, PSWQ, EPDS and Y-BOCS scores correlated negatively with FT4 concentrations (p < 0.010, r = −0.768; p < 0.010, r = −0.384; p < 0.050, r = −0.364; p < 0.010, r = −0.544, respectively). At the 3rd trimester, BLUES score correlated positively with rT3 concentrations (p = 0.00, r = 0.89); GADI, EPDS, and Y-BOCS scores correlated negatively with FT4 concentrations (p = 0.001, r = − 0.468; p = 0.036, r = −0.39; p = 0.001, r = −0.625, respectively); GADI, STAI-S, and Y-BOCS scores correlated positively with TSH concentrations (p = 0.015, r = 0.435; p = 0.024, r = 0.409 p = 0.041, r = 0.389, respectively). At postpartum, PSWQ, STAI-T, EPDS, and BDI scores correlated positively with rT3 concentrations (p = 0.024, r = 0.478; p = 0.014, r = 0.527; p = 0.046, r = 0.44; p = 0.021, r = 0.556, respectively, Y-BOCS score correlated positively with TSH (p = 0.045, r = 0.43), and BLUES score correlated positively with anti-TPO antibody concentrations (p = 0.070, r = 0.586). Conclusion The reported findings demonstrate positive associations between low-normal thyroid function at the 2nd and 3rd trimesters of pregnancy and postpartum with anxiety, depression, and OCD scores.